38 mm diameter cold bore metal-as-insulation HTS insert reached 32.5 T in a background magnetic field generated by resistive magnet. (March 2020) - Fazilleau, Philippe; Chaud, Xavier; Debray, François; Lécrevisse, Thibault; Song, Jung-Bin
Highlights: An HTS insert with a 50 mm inner bore was designed and fabricated. The Metal-as-Insulation winding technology is used. It was successfully tested up 30 T, its initial objective. It also generates 32.5 T, record for a HTS insert with a useful diameter of 38 mm. It survived a quench at the magnetic field of 32.5 T. Abstract: A 38 mm diameter cold bore High Temperature Superconducting solenoidal insert was designed, constructed and tested by a collaborative team of CEA-CNRS researchers. With a design based on the Metal-as-Insulation (MI) winding technique, the HTS magnet is made of 9 double pancakes of a 6 mm wide tape and intended to operate at a central magnetic field of 30 T, generating 10T by itself. Its overall diameter and height are 125 mm and 255 mm respectively, making it very compact. In liquid helium at 4.2 K, the magnet operated twice at the central magnetic field target of 30 T, of which 12T were generated by the insert alone. It also set a new record for the operation of HTS insert with a 38 mm useful diameter, operating in a central magnetic field of 32.5 T, of which 14.5 T were generated by the insert alone. These results demonstrate the strong potential of MI-HTS magnets for the production of very intense magnetic fields.